The Roles of Social Media in Hypertension Management Programs - Pandit Bagus Tri Saputra; Sherly Yolanda; Dinda Dwi Purwati; Sulistiawati (Cermin Dunia Kedokteran, 2022)
Hypertension is still one of the leading causes of morbidity and mortality globally. Complications of hypertension cause innumerable social, economic, and health cost burdens, reaching 131 million dollars per year in the United States. However, blood pressure control through lifestyle modifications and pharmacological intervention, achieving blood pressure targets is often unsatisfying. With its simple, cost-efficient, multifunctional, and enormous coverage characteristics, social media is promising to be utilized in health programs. Social media could provide massive information and accommodate the hypertension community to increase hypertension awareness. Incorporating social media in hypertension management improves patients’ lifestyles and pharmacological adherence more than conventional methods. The exact mechanism of how social media-based health programs increase treatment adherence is complex and has not been well-defined; raised awareness, bidirectional communication, and a qualified coach (physician) seem to be the essential factors. It should also be well aware that screen time duration and emotional alteration due to social media exposure could also potentially increase blood pressure. Hipertensi masih menjadi salah satu penyebab utama morbiditas dan mortalitas global. Komplikasi hipertensi menimbulkan beban sosial, ekonomi, dan biaya kesehatan yang mencapai 131 juta dollar setiap tahun di Amerika Serikat. Kontrol tekanan darah melalui modifikasi gaya hidup dan intevensi farmakologis, hasilnya seringkali masih belum memuaskan. Media sosial dengan karakteristiknya yang simpel, murah, multifungsi, dengan cakupan sangat luas tampak menjanjikan untuk digunakan dalam program-program kesehatan. Media sosial dapat menyediakan berbagai informasi dan mengakomodasi komunitas untuk meningkatkan kesadaran terhadap hipertensi. Penggunaan media sosial dalam manajemen hipertensi tampak mampu memperbaiki pola hidup dan ketaatan farmakologi lebih baik daripada metode konvensional. Mekanisme pastinya bersifat kompleks dan masih belum dapat dijelaskan dengan baik; namun peningkatan kesadaraan, komunikasi dua arah, dan pendamping (dokter) terkualifikasi tampak sebagai faktor-faktor penting. Hal yang seharusnya juga diperhatikan adalah durasi screen time dan perubahan emosional karena saat menggunakan media sosial juga dapat berpotensi meningkatkan tekanan darah.